Neurodevelopmental delay in children exposed to maternal SARS-CoV-2 in-utero - Fajardo-Martinez, Viviana; Ferreira, Fatima; Fuller, Trevon; Cambou, Mary Catherine; Kerin, Tara; Paiola, Sophia; Mok, Thalia; Rao, Rashmi; Mohole, Jyodi; Paravastu, Ramya; Marschik, Dajie; Marschik, Peter B.; et al. (Scientific reports, 2024)
It is unclear if SARS CoV-2 infection during pregnancy is associated with adverse neurodevelopmental repercussions to infants. We assessed pediatric neurodevelopmental outcomes in children born to mothers with laboratory-confirmed SARS CoV-2 infection during pregnancy. Neurodevelopmental outcomes of in-utero exposed children were compared to that of pre-pandemic control children in Los Angeles (LA), CA, USA and Rio de Janeiro, Brazil. Bayley Scales of Infant and Toddler Development, 3rd edition (Bayley-III), the gold standard tool for evaluating neurodevelopment until 36 months of age and Ages and Stages Questionnaires (ASQ-3), a frequently used screening instrument for evaluating neurodevelopment in this same age group were the assessment tools used. Developmental delay (DD) was defined as having a score < − 2 SD below the norm (< 70) in at least one of three Bayley-III domains, (cognitive, motor or language) or a score below the cut-off (dark zone) in at least one of five ASQ-3 domains (communication, gross motor, fine motor, problem solving, personal-social). Exposed children were born between April 2020 and December 2022 while control children were born between January 2016 to December 2019. Neurodevelopmental testing was performed in 300 children total: 172 COVID-19 exposed children between 5-30 months of age and 128 control children between 6-38 months of age. Bayley-III results demonstrated that 12 of 128 exposed children (9.4%) had DD versus 2 of 128 controls (1.6%), p = 0.0007. Eight of 44 additional exposed children had DD on ASQ-3 testing. Fully, 20 of 172 exposed children (11.6%) and 2 of 128 control children (1.6%), p = 0.0006 had DD. In Rio, 12% of exposed children versus 2.6% of controls, p = 0.02 had DD. In LA, 5.7% of exposed children versus 0 controls, p = 0.12 had DD. Severe/critical maternal COVID-19 predicted below average neurodevelopment in the exposed cohort (OR 2.6, 95% CI 1.1-6.4). Children exposed to antenatal COVID-19 have a tenfold higher frequency of DD as compared to controls and should be offered neurodevelopmental follow-up.